Improving the Post-polymerization Modification of Bio-Based Itaconate Unsaturated Polyesters: Catalyzing Aza-Michael Additions With Reusable Iodine on Acidic Alumina - Moore, Oliver B.; Hanson, Polly-Ann; Comerford, James W.; Pellis, Alessandro; Farmer, Thomas J. (Frontiers in Chemistry, 2019)
Bio-based platform molecules such as itaconic, fumaric, and muconic acid offer much promise in the formation of sustainable unsaturated polyester resins upon reaction with suitable diols and polyols. The C=C bonds present in these polyester chains allows for post-polymerization modification and such moieties are conventionally utilized in curing processes during the manufacture of coatings. The C=C modification sites can also act as points to add useful pendants which can alter the polymers final properties such as glass transition temperature, biodegradability, hardness, polarity, and strength. A commonly observed modification is the addition of secondary amines via an aza-Michael addition. Conventional procedures for the addition of amines onto itaconate polyesters require reaction times of several days as a result of undesired side reactions, in particular, the formation of the less reactive mesaconate regioisomer. The slow reversion of the mesaconate back to itaconate, followed by subsequent amine addition, is the primary reason for such extended reaction times. Herein we report our efforts toward finding a suitable catalyst for the aza-Michael addition of diethylamine onto a model substrate, dimethyl itaconate, with the aim of being able to add amine onto the itaconate units without excessive regioisomerization to the inactive mesaconate. A catalyst screen showed that iodine on acidic alumina results in an effective, heterogeneous, reusable catalyst for the investigated aza-Michael addition. Extending the study further, itaconate polyester was prepared by Candida Antartica Lipase B (CaL-B) via enzymatic polytranesterification and subsequently modified with diethylamine using the iodine on acidic alumina catalyst, dramatically reducing the required length of reaction (>70% addition after 4 h). The approach represents a multidisciplinary example whereby biocatalytic polymerization is combined with chemocatalytic modification of the resultant polyester for the formation of useful bio-based polyesters.